METABOLIC SURGERY IN TREATMENT OF DIABETES MELLITUS OF TYPE II - V. M. Sedov; M. B. Fishman (Вестник хирургии имени И.И. Грекова)
Nowadays, according to data of WHO, the diabetes mellitus was diagnosed in more than 280 million people. The diabetes mellitus type II had 90% patients. The applied methods of conservative therapy seldom lead to euglycemia condition of patients. Last years the treatment of diabetes mellitus was carried out by the method of different bariatic interventions. Good results was obtained, they should be analyzed and investigate. The results of treatment of 142 patients from 628 patients (with type II) were estimated. The patients were undergone by different bariatic interventions. Modern laparoscopic operations were performed on all the patients. Controlled bandage of stomach had 81 of patients. Gastric resection was performed in 28. Gastric bypass surgery was carried out in 22 of patients and biliopancreatic diversion — in 11. The improvement of control of leukemia level was obtained. Diabetes type II could be treated by surgical methods. The best results were obtained after combined operations, which potentially could present an alternative method of treatment of type II diabetes.